Adapted Physical Activity Applications from the Perspective of Special Education Center Administrators: A Phenomenological Approach - SAROL, Halil; GÜLOĞLU, Nazlı; GÜRKAN, Rıfat Kerem; BUDAK, Davut (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2022)
The aim of this research is to examine the perspectives of special education centers on adapted physical activity applications. In this qualitative study, which was designed in a phenomenological pattern, the criterion sampling method, one of the purposive sampling methods, was used. In line with the determined criteria, the study group of the research consists of 10 (ten) special education center administrators who implement adapted physical activity programs in Ankara. Personal information form and semi-structured interview form were used as data collection tools in the research. In the research, face-to-face interviews were conducted with the administrators of special education centers in the study group. The data were analyzed using the content analysis method. In order to ensure reliability in the research, Miles and Huberman’s (1994) reliability formula was used and it was found to be .85. According to the research findings; The fact that adapted physical activity applications in special education centers contribute to individuals with physical, psychological, social and academic needs plays an important role in including these practices. In addition, it is seen that the provision of adapted physical activity services is an important factor in the preference of individuals with special needs by their parents. In this respect, it is stated that centers include adapted physical activity practices in their curricula and create the content of existing applications in line with the needs of individuals. It is seen that centers give importance to field arrangement, equipment selection and selection of qualified trainers for adapted physical activity practices. As a result, it can be said that adapted physical activity in special education centers contributes a lot to individuals with special needs, and adapted physical activity applications are important in choosing centers.